2008
DOI: 10.1182/blood-2007-06-094318
|View full text |Cite
|
Sign up to set email alerts
|

Differential in vivo potential of endothelial progenitor cells from human umbilical cord blood and adult peripheral blood to form functional long-lasting vessels

Abstract: Tissue engineering requires formation of a de novo stable vascular network. Because of their ability to proliferate, differentiate into endothelial cells, and form new vessels, blood-derived endothelial progenitor cells (EPCs) are attractive source of cells for use in engineering blood vessels. However, the durability and function of EPC-derived vessels implanted in vivo are unclear. To this end, we directly compared formation and functions of tissue-engineered blood vessels generated by peripheral blood-and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
271
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(285 citation statements)
references
References 14 publications
11
271
0
3
Order By: Relevance
“…3A-D). In agreement with previous observations (22,25,26), when constructs with HUVECs alone were implanted, circular structures formed by day 4 after implantation, but the engineered vessels appeared counterfeit, remained immature, and eventually regressed. Implanted constructs generally showed relative behavior similar to in vitro culture, with endothelial-only scaffolds showing poor survival and marginal lumen formation and no evidence of anastomosis.…”
Section: Formation Of Engineered Vessels Within the 3d Porous Scaffolsupporting
confidence: 78%
“…3A-D). In agreement with previous observations (22,25,26), when constructs with HUVECs alone were implanted, circular structures formed by day 4 after implantation, but the engineered vessels appeared counterfeit, remained immature, and eventually regressed. Implanted constructs generally showed relative behavior similar to in vitro culture, with endothelial-only scaffolds showing poor survival and marginal lumen formation and no evidence of anastomosis.…”
Section: Formation Of Engineered Vessels Within the 3d Porous Scaffolsupporting
confidence: 78%
“…We previously reported successful generation of durable engineered blood vessels in vivo using HUVECs (19) or ECs derived from cord blood-derived EPCs (26) or hESCs (20). In all cases, coimplantation with murine MPC 10T1/2 cells (19,20,26) or human MSCs (29) was required to sustain these engineered blood vessels in vivo. Translation of our previous findings will thus require patientcompatible sources of both ECs and mesenchymal cells in a large quantity.…”
Section: Discussionmentioning
confidence: 99%
“…S9) with 10T1/2 MPCs in vivo using the tissue-engineered model in the cranial window of SCID mice (26,27). We found that T1D-iPS cell-derived ECs could generate a functional vasculature within 2 wk of coimplantation.…”
mentioning
confidence: 98%
“…Many studies have verified the ability of MSCs in supporting the long-term survival and stability of endothelial cells [16], [17] when they are co-cultured in the same niche. Stable and functional blood vessel network can be regenerated in vivo by injecting mixed mesenchymal precursor cells and HUVECs, whereas tubular network formed by HUVECs alone tend to regress and disappear over time [12].…”
Section: B Cell Morphologymentioning
confidence: 99%